22.1: Fabrication of Broadband Quarter Wave Plate by Combination of Two Retardation Films Using Coating Technique. (28th November 2018) - SUN, Zhibo; Meng, Cuiling; HO, Jacob; TSENG, Ken; KWOK, Hoi-Sing
Abstract : Broadband quarter waveplate can be treated as a circular polarizer providing true dark in the display system. Broadband quarter wave plate consists of two waveplates with different alignment direction using coating technique is proposed and fabricated. The reflection spectrum shows a good dark state